Development of e-module based on problem-based learning theme of substance pressure to grow students problem-solving ability in Junior High School - Ida Trianawati; Vica Dian Aprelia Resti; Dwi Indah Suryani (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
The implementation of Natural Sciences learning is not only limited to the ability of students to remember and passively pay attention to the teacher's presentation, but in learning natural sciences, students must participate and play an active role in finding out the concepts that will be and are being studied so that in practice it requires a method for solving problems about nature systematically. To overcome these problems, the thing that can be done is to apply Problem-Based Learning to foster students' problem-solving abilities. The purpose of this study was to describe the level of validity and readability of the E-Module based on Problem-Based Learning with the Theme of Substance Pressure to Grow the Problem-Solving Ability of Grade VIII Middle School Students. This development research uses the Thiagarajan development model, which consists of 3 stages: define, design, and develop. The subjects in this study were 2 expert lecturers, 2 materials and teaching materials experts, 3 expert practitioners, namely natural science teachers, and 30 class VIII students. Data from the study were collected using interview sheets, validation sheets, and readability questionnaire sheets. The results of the validity of the E-Module were obtained with an average percentage of 87.25% with a very valid category. After being revised, a readability test was carried out on students, and the result was 90.65% with a very good category so that the E-Module created contains material and language that is easy to understand, as well as the writing of letters and pictures according to the material.